An Evaluation of PROMIS Health Domains in Sarcoma Patients Compared to the United States Population. (16th January 2019) - Wilke, Benjamin; Cooper, Anna; Scarborough, Mark; Gibbs, C. Parker; Spiguel, Andre
Abstract : Background . The Patient Reported Outcomes Measurement Information System (PROMIS) is a patient-directed system that allows comparisons across medical conditions. With this tool, comparisons can now be made between rare conditions, such as sarcomas, and more common ailments, of the United States general population. This allows comparisons between rare conditions, such as sarcomas, to more common ailments, or even the United States (US) general population. Objectives . Our purpose was to use PROMIS to compare outcomes in patients that had undergone resection of a nonmetastatic sarcoma to the US population. Methods . One hundred thirty-eight patients were included in the analysis. These patients were divided into early (<2 years) and late follow-up (>2 years). Results . We evaluated results from seven health domains and found significantly lower scores in the physical function and depression domains. These differences were present in both the early and late cohorts when compared to the US population. Conclusion . While physical function was found to be worse in the sarcoma cohorts, we observed significantly improved levels of depression in these patients when compared to the US population. This finding was maintained over time and is an important reminder that a patient's goals and desires change following a cancer diagnosis and must be taken into consideration when planning treatment and determining a successful outcome.